Two new species of Folsomia from north-eastern China (Collembola, Isotomidae) - Wang, Baifeng; Wu, Donghui (Zootaxa, 2012)
Two new species Folsomia aquatica sp. nov. and Folsomia sanjiangensis sp. nov. from north-eastern China are described. F. aquatica was only found in wetlands, it belongs to quadrioculata-group, it can be distinguished from other species in the group by the combination of the following characters: ommatidia absent; microsensillar formula as1,1/1,0,0; VT with 4+4 latero-distal and usually 7 (6–10) posterior chaetae; 1+1 chaeta on anterior side of manubrium. F. sanjiangensis was found in forest and wetlands, it belongs to sensibilis-group and characterized by ommatidia absent; median sensilla on abdomen within p-row of chaetae; fifth segment of abdomen with a pair of leaf-like sensilla on each side; and 3 chaetae on lateral sides of manubrium.